Digitalization and regional integration: comparative analysis of the EU and EAEU experience - Mussina, Г.С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
In the context of global and local geopolitical crises, the introduction of digital technologies into the life of society encourages us to reconsider the course of many processes. The transition to digital public administration, digital business, and digital mobility of citizens is changing the usual approaches to assessing the development of countries and regions of the world. The new opportunities of the digital economy both make it possible to simplify business processes and have potential risks. However, it is obvious that in the context of international integration processes, digital transformation entails the removal of barriers and contributes to the positive implementation of integration tools. This article presents a study of the relationship between digitalization and regional integration based on content analysis and a comparative approach. In particular, the introduction of digital technologies to enhance interaction between countries at the supranational level within the framework of integration associations is assessed on the basis of the cases of the European Union and the Eurasian Economic Union. According to the authors, the use of digital cooperation tools, the opportunities that the Internet and digitalization bring have a positive economic and social effect. At the national level, the development of innovations and new technologies is stimulated, at the supranational level, areas of cooperation are expanding, trade processes are intensifying, and procedures for the movement of people, goods, and services are simplified. In addition, investments in the IT sector can generally provide GDP growth for both countries and regional associations. In this regard, it is concluded that it is necessary to use digitalization as a new tool for strengthening integration processes and for ensuring the sustainable development of regions